Automated Calculations for Improvement of Tank Inventory at Fuel Terminals - Sulaiman, S. A.; Basil, Sherrene C.; Dunggatt , Nelson S.; Hashim , Mohd Hafriz M. (2010)
The business related to downstream petroleum products is highly competitive, and thus any losses in handling the transfer of these products at fuel terminals, regardless of the size, would significantly affect the income of the petroleum product distributor involved. With proper inventory, a distributor may be able to manage the fluctuations in demand and lead time, and eventually benefit a good control of stock and money. Petroleum products are volatile and sensitive to changes in temperatures. Hence, an inability to correct the measured volumes of products to the applicable standards will result in deviation from the actual quantity at site, which can be either loss or gain in income. Inaccuracies in the calculation and recording of measurements are partly caused by one or a combination of a few human errors. The present work is intended to minimize the errors related to human and consequently improve the quality of work performance at fuel terminals by using a reliable automated calculation system for quantification of volumes of petroleum products. This system is developed in a Microsoft Excel file, with features such as automatic data look-up, interpolations and a neat recording system. The system will correct the measurements to standard temperatures according to the type of tasks. It is found that the system is able to reduce the calculation time of the physical stock at the standard temperature at the fuel terminal by up to 21 times. More importantly, the system is shown to reduce the human errors detected from the past record.